Análisis de la ley orgánica del sistema nacional de contratación pública en los procesos de adquisiciones emergentes durante la pandemia covid- 19 del hospital general Quevedo, año 2020 - García Paredes, Débora Johanna (2023)
The main objective of this research is to analyze the Organic Law of the National Public Procurement System in the emerging procurement processes during the Covid-19 pandemic of the Quevedo General Hospital, year 2020. The theoretical framework is based on conceptual definitions, theories and legal contributions. The methodology that was applied in the research is inductive, deductive, and descriptive, as well as qualitative and quantitative. Techniques used: observation, interview and survey. An assessment matrix was developed on the level of training of users in public procurement regulations, the problem was followed up establishing the incidence of the Organic Law of the National Public Procurement System in the emerging procurement processes during the pandemic, to comply with the objectives: it is determined that internal users agree to receive training on the management of regulations for public procurement processes, during the pandemic no specific budget was assigned, the established one was used, therefore budgetary compliance in the emerging contracting requirements was 79%, when quantifying the indicators, the level of compliance with the contracting guidelines in the acquisition of requirements reached 64%, and the level of compliance with the contracting levels was established at 73%. It is concluded that the contracting law has a direct impact on the purchase processes of medicines and supplies, strengthen compliance with the existing training schedule and maintain budget performance in emerging acquisitions, follow the guidelines and management policies to formalize the requirements. necessary to perform the processes properly.